(untitled) (Libellarium: journal for research in the field of information and related sciences, 2021)
Public libraries should be community centres that nurture cultural development, lifelong learning and socializing. All of these aspects are typical for library events. This paper presents research into how travel-related events support a library’s mission, how they are organized, promoted and how users view them. Several studies were conducted in Mestna knjižnica Ljubljana (MKL) at travel-related events in 2015 and 2016, including interviewing ten librarians and four users, questionnaire survey with 160 participants and analysis of 129 travel-related events. The results revealed that travel-related events are frequently organized in all branches of MKL, they are well visited and users are generally satisfied with them. However, there is still room for improvement in organization and promotion of events. Furthermore, this paper argues that this type of event is a good opportunity to help fulfil the library mission and bring people into the library.